2016
DOI: 10.1089/ast.2016.1537
|View full text |Cite
|
Sign up to set email alerts
|

Modeling pN2 through Geological Time: Implications for Planetary Climates and Atmospheric Biosignatures

Abstract: Nitrogen is a major nutrient for all life on Earth and could plausibly play a similar role in extraterrestrial biospheres. The major reservoir of nitrogen at Earth's surface is atmospheric N 2 , but recent studies have proposed that the size of this reservoir may have fluctuated significantly over the course of Earth's history with particularly low levels in the Neoarchean -presumably as a result of biological activity. We used a biogeochemical box model to test which conditions are necessary to cause large sw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 113 publications
7
74
0
Order By: Relevance
“…The chemical composition and physical structure of Earth's ancient atmosphere are active areas of research because these properties can leave perceptible imprints on rocks (Rasmussen & Buick, 1999;Som, Catling, Harnmeijer, Polivka, & Buick, 2012;Som et al, 2016). Independent methods, including paleobarometric measurements (Busigny, Cartigny, & Philippot, 2011;Som et al, 2012;Marty, Zimmerman, Pujol, Burgess, & Philippot, 2013;Som et al, 2016;Avice et al, 2018; summarized schematically in Figure 1) and modeling efforts (Barry & Hilton, 2016;Berner, 2006;Goldblatt et al, 2009;Johnson & Goldblatt, 2017Mallik, Li, & Wiedenbeck, 2018;Stüeken, Kipp, Koehler, Schwieterman et al, 2016), have attempted to constrain pN 2 throughout Earth's history. Several nitrogen sources and sinks control the atmospheric nitrogen concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition and physical structure of Earth's ancient atmosphere are active areas of research because these properties can leave perceptible imprints on rocks (Rasmussen & Buick, 1999;Som, Catling, Harnmeijer, Polivka, & Buick, 2012;Som et al, 2016). Independent methods, including paleobarometric measurements (Busigny, Cartigny, & Philippot, 2011;Som et al, 2012;Marty, Zimmerman, Pujol, Burgess, & Philippot, 2013;Som et al, 2016;Avice et al, 2018; summarized schematically in Figure 1) and modeling efforts (Barry & Hilton, 2016;Berner, 2006;Goldblatt et al, 2009;Johnson & Goldblatt, 2017Mallik, Li, & Wiedenbeck, 2018;Stüeken, Kipp, Koehler, Schwieterman et al, 2016), have attempted to constrain pN 2 throughout Earth's history. Several nitrogen sources and sinks control the atmospheric nitrogen concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found a mantle nitrogen abundance of 7 ± 4 times the present atmospheric level (Johnson & Goldblatt, ) and coupled with modern subduction recycling rates (Mallik et al, ), these imply that the mantle is a long‐term sink of atmospheric nitrogen that has been monotonically sequestered over time. However, modern fluxes only apply if redox conditions were constant through time, yet models including nitrogen speciation change indicate that redox has a substantial effect on the atmospheric reservoir (Laneuville et al, ; Stüeken et al, ). The stable form of deep sea nitrogen for the Archean would have been NH 4 + (Holland, ), not oxidized species like NO 3 − as in modern oceans.…”
Section: Atmospheric Density In the Archeanmentioning
confidence: 99%
“…However, pN 2 may have fluctuated over the course of Earth's ~4.5 billion-year history. Modeling work has demonstrated that large (>0.1 bar) pN 2 fluctuations are plausible on >10 7 year timescales under reasonable estimates of biogeochemical fluxes (Busigny, Cartigny, & Philippot, 2011;Goldblatt et al, 2009;Johnson & Goldblatt, 2018;Mallik, Li, & Wiedenbeck, 2018;Stüeken, Kipp, Koehler, Schwieterman, et al, 2016). Such large changes in pN 2 would carry implications for global climate due to the effect of pressure broadening on the absorption of infrared radiation by greenhouse gases in the troposphere (Goldblatt et al, 2009;Stüeken, Kipp, Koehler, Schwieterman, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Modeling work has demonstrated that large (>0.1 bar) pN 2 fluctuations are plausible on >10 7 year timescales under reasonable estimates of biogeochemical fluxes (Busigny, Cartigny, & Philippot, 2011;Goldblatt et al, 2009;Johnson & Goldblatt, 2018;Mallik, Li, & Wiedenbeck, 2018;Stüeken, Kipp, Koehler, Schwieterman, et al, 2016). Such large changes in pN 2 would carry implications for global climate due to the effect of pressure broadening on the absorption of infrared radiation by greenhouse gases in the troposphere (Goldblatt et al, 2009;Stüeken, Kipp, Koehler, Schwieterman, et al, 2016). For this reason, there has been considerable effort in recent years to constrain pN 2 using geological proxies that are sensitive to atmospheric pressure (e.g., Som, Catling, Harnmeijer, Polivka, & Buick, 2012;Som et al, 2016;Goosmann, Catling, Som, Altermann, & Buick, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation